Respuesta :

By the polynomial remainder theorem, the remainder of [tex]P(x)[/tex] upon dividing by [tex]x+3[/tex] is equal to the value of [tex]P(-3)[/tex].

Synthetic division yields

-3   |   1    0    0     -4     4

.      |       -3    9   -27   93

- - - - - - - - - - - - - - - - - - -

.      |   1   -3    9   -31    97

which translates to

[tex]\dfrac{x^4-4x+4}{x+3}=x^3-3x^2+9x-31+\dfrac{97}{x+3}[/tex]

[tex]\implies x^4-4x+4=(x+3)(x^3-3x^2+9x-31)+97[/tex]

Then when [tex]x=-3[/tex], the first term on the right side vanishes and we have [tex]P(-3)=97[/tex].

ACCESS MORE